On Adverbs in the Cynegetica of ps.Oppian - Mersinias, Stamatis (Myrtia, 2017)
In this paper, I discuss, in four sub-sections, the use of adverbs in ps.Oppian’s Cynegetica; in the first part, I examine adverbs in -ως, -δον, -δην, -δις. The second section deals with adverbial formations in -τι, -φι, -κι, θι, and –θις, the examination focusing on the way these adverbs are used, on morphological peculiarities and matters of prosody, on the lexemes they modify in the Cynegetica, as well as on their relative frequency on analogy with the rest of Greek epic poetry. In the third part, I discuss the use of the article with an adverb, and in the last one the juxtaposition of adverbs in the Cynegetica is examined.